Pengaruh Kualitas Informasi dan Teknologi Informasi terhadap Kinerja Rantai Pasok Melalui Penerapan Berbagi Informasi - Vincent, Vincent; Laulita, Nasar Buntu (Jurnal Maksipreneur, 2025)
In this study, technological advances have encouraged the use of AI-based systems in various activities. This study examines how AI can simplify company work and help solve problems related to supply chain performance, thereby improving company performance with the support of information quality, information technology, and information sharing, which helps the smooth running of the supply chain for the advancement of the company. This research facilitates the identification of key problems and their effective resolution. This research uses quantitative data obtained from a community survey in Batam. The results obtained from AI can facilitate various things for companies. The results of this study show that the influence of information quality and information technology on supply chain performance through the application of information sharing is significant. This improves performance within companies using current technology.